2016
DOI: 10.1189/jlb.4a0915-428r
|View full text |Cite|
|
Sign up to set email alerts
|

Antibody blockade of IL-17 family cytokines in immunity to acute murine oral mucosal candidiasis

Abstract: Antibodies targeting IL-17A or its receptor, IL-17RA, are approved to treat psoriasis and are being evaluated for other autoimmune conditions. Conversely, IL-17 signaling is critical for immunity to opportunistic mucosal infections caused by the commensal fungus Candida albicans, as mice and humans lacking the IL-17R experience chronic mucosal candidiasis. IL-17A, IL-17F, and IL-17AF bind the IL-17RA-IL-17RC heterodimeric complex and deliver qualitatively similar signals through the adaptor Act1. Here, we used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
4
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(85 citation statements)
references
References 74 publications
1
78
4
2
Order By: Relevance
“…Antibodies targeting IL-17A or its receptor, IL-17RA, are approved to treat psoriasis and are being evaluated for other autoimmune conditions [53, 54]. We found that intravitreal treatment with anti-IL-17A-neutralizing mAb alleviated DR-like pathology, including retinal Müller cell activation and dysfunction, BRB breakdown, and retinal ganglion cell apoptosis.…”
Section: Discussionmentioning
confidence: 67%
“…Antibodies targeting IL-17A or its receptor, IL-17RA, are approved to treat psoriasis and are being evaluated for other autoimmune conditions [53, 54]. We found that intravitreal treatment with anti-IL-17A-neutralizing mAb alleviated DR-like pathology, including retinal Müller cell activation and dysfunction, BRB breakdown, and retinal ganglion cell apoptosis.…”
Section: Discussionmentioning
confidence: 67%
“…This may simply mean that blockade is incomplete, due either to dose effects or access of anti-IL-17 antibodies to the oral mucosal tissue. Alternatively, these biologics spare IL-17F, which has been shown to cooperate with IL-17A in promoting resistance to OPC [63,78]. Cumulatively, these findings all support a central role for IL-17 receptor signal transduction in mucosal host defense, at both innate and adaptive levels.…”
Section: Innate Immunity At Mucosal Surfaces: Innate Type 17 Cellsmentioning
confidence: 95%
“…IL-17A is dominant in the requirement for control of C. albicans OPC infection in mice, although IL-17F and IL-17AF may also contribute to protection [113]. Notably, a mutation in the IL17F gene was recently reported in a family with CMC [114].…”
Section: Il-17 Family Cytokines In Host Protection and Inflammationmentioning
confidence: 99%